ANALISIS PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marzulina, Evri Dwi; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to determine the effect of liquidity (CR) and solvency (DAR) on financial performance (ROA) in the ceramic, porcelain and glass sub-sector, cement sub-sector and metal sub-sector and the like. The data analysis technique used in this research is quantitative analysis which includes classical assumption tests, multiple linear analysis, coefficient of determination and hypothesis testing. The results of the study can be concluded as follows: 1) The results of multiple linear regression, namely Y = 0.088 + 0.005CR – 0.09DAR + e, CR has a positive effect on ROA while DAR has a negative effect on ROA. 2) The results of the analysis of the coefficient of determination state that CR and DAR are able to explain the ROA variable by 38%, while 62% can be used as other variables that are not discussed in this study. 3) The results of the f test state that liquidity (CR) and solvency (DAR) simultaneously have a significant effect on financial performance (ROA). 4) The results of the t test state that liquidity (CR) has no and insignificant effect on financial performance (ROA) while solvency (DAR) has a significant and significant effect on financial performance (ROA).